Electroplating method of plug shielding piece
Through multi-physics collaborative optimization technology and post-treatment technology, the problems of insufficient adhesion, incomplete cleaning effect and uneven coating thickness of traditional electroplating technology on the plug shields of complex geometric structures are solved, and the uniformity, coverage and corrosion resistance of the coating are significantly improved.
Patent Information
- Application Number
- CN202510089023.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-01-21
AI Technical Summary
When dealing with plug shields with complex geometric structures, traditional electroplating technology has problems such as insufficient adhesion, incomplete cleaning effect and uneven coating thickness, resulting in poor performance in product service life and anti-interference performance.
Multi-physics field collaborative optimization technology is adopted to regulate the electric field distribution through the main electrode and the auxiliary electrode, combine the magnetic field and the flow field to optimize the migration of metal ions, plating is performed using pulse current, and passivation, drying and curing is performed in post-processing to improve the adhesion, uniformity and corrosion resistance of the plating layer.
It significantly improves the adhesion and uniformity of the coating, enhances the coverage of complex geometric surfaces, improves the corrosion resistance and stability of the coating, and solves the problems of uneven coating thickness and insufficient coverage of deep holes in traditional technology.
Smart Images

Figure CN119615317A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electroplating, and in particular to an electroplating method for a plug shielding part. Background Art
[0002] As modern electronic devices develop towards miniaturization, high integration and high performance, plug shields, as an important component of electrical connectors, have a surface plating layer whose quality is directly related to the anti-interference performance, corrosion resistance and service life of the equipment. Traditional electroplating technology mainly relies on single DC deposition, which can basically meet the requirements in past application scenarios. However, with the increasing complexity of the geometric structure of plug shields and the harshness of environmental conditions, the limitations of this traditional technology are becoming increasingly apparent.
[0003] In the prior art, conventional electroplating processes generally use a single main electrode direct current deposition method, which mainly deposits metal ions on the surface of the plug shield through a static electric field. However, due to the non-uniformity of the electric field distribution, over-deposition is prone to occur at the edge of the plug shield, while insufficient deposition occurs in the groove and deep hole areas. This phenomenon is called the "edge effect", which directly leads to the uneven thickness of the coating. Uneven thickness not only affects the shielding performance, but may also cause product failure due to the exposure of local weak areas. In particular, for plug shields with complex geometries, such as structures with deep holes or multiple grooves, the traditional electroplating method has extremely limited coverage of deep holes and recessed areas. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides an electroplating method for a plug shielding component, which solves the problems of insufficient adhesion and incomplete cleaning effect in complex geometric surface treatment.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: A method for electroplating a plug shielding member, comprising the following steps: Performing surface pretreatment on the plug shield; Placing the plug shield in an electrolyte for electroplating, wherein the electric field distribution is regulated by a main electrode and an auxiliary electrode during the electroplating process, and the magnetic field and the flow field are combined for optimization; The electroplated plug shield is passivated, cleaned, dried and cured.
[0006] Preferably, the surface pretreatment comprises the following steps: Ultrasonic cleaning is performed in an ethanol solution for 8 to 12 minutes at a temperature of 25 to 30°C; The surface of the plug shield is treated using argon plasma, with a pressure range of 0.05 to 0.15 MPa, a power range of 50 to 150 W, and a time of 2 to 5 minutes; The acid activation treatment is carried out in a 10% sulfuric acid solution for 1 to 3 minutes at a temperature of 25 to 35°C.
[0007] Preferably, in the electroplating step, the main electrode is used to provide a stable current density in the range of 2.0 to 2.5 A / dm 2 The auxiliary electrode is arranged at the edge and groove area of the plug shielding part to dynamically control the local electric field. The potential range of the auxiliary electrode is 0 to 0.5V.
[0008] Preferably, in the electroplating step, the components of the electrolyte include: Nickel sulfate, concentration is 280-320 g / L; Nickel chloride, concentration is 40-50 g / L; Boric acid, concentration is 25-35 g / L; Polyethylene glycol, concentration is 40-60ppm.
[0009] Preferably, a magnetic field is used to enhance ion migration in the electroplating step, and the magnetic field is generated by an electromagnetic coil, the magnetic field strength ranges from 0.2 to 0.4 T, and the direction of the magnetic field is orthogonal to the direction of the electric field.
[0010] Preferably, in the electroplating step, a turbulent flow is generated in the deep hole and groove areas of the plug shielding component by a microfluidic nozzle, the flow rate of the microfluidic nozzle ranges from 0.2 to 0.5 m / s, and the nozzle spray angle ranges from 30° to 60°.
[0011] Preferably, the electroplating step uses a pulse current for electroplating, the pulse frequency range is 300-500 Hz, and the peak current density is 2.5-3.5 A / dm 2 , the ratio of on-time to off-time is 1:1~1:2.
[0012] Preferably, the electroplating time is 8 to 12 minutes, and the thickness of the final coating is controlled at 6±0.5 μm.
[0013] Preferably, the passivation treatment in the post-treatment is carried out in an alkaline solution with a pH value of 9 to 10, and the passivation time is 2 to 4 minutes.
[0014] Preferably, the drying treatment in the post-treatment is carried out at a constant temperature of 70 to 90° C. for 0.5 to 1 hour.
[0015] The present invention provides an electroplating method for a plug shielding member, which has the following beneficial effects: 1. The present invention adopts the surface pretreatment technical scheme of cleaning, argon plasma treatment and acid activation, removes surface impurities through ultrasonic cleaning, enhances surface activity through plasma etching, and further optimizes surface roughness through acid activation, achieving the technical effect of significantly improving the adhesion of the electroplating layer and the uniformity of the plating layer. Compared with the technical scheme of the prior art that simply relies on chemical cleaning, it solves the problems of insufficient adhesion and incomplete cleaning effect in the treatment of complex geometric surfaces.
[0016] 2. The present invention realizes electric field distribution control through the main electrode and the auxiliary electrode, and strengthens the metal ion migration and coverage of the deep hole area by combining the effects of the magnetic field and the flow field, achieving the technical effect of significantly improving the uniformity of the coating thickness and the coating coverage rate of the groove deep hole area. Compared with the electroplating method in the prior art that only uses fixed electrodes or static plating solutions, it solves the problems of uneven coating thickness and insufficient deep hole coverage.
[0017] 3. The present invention adopts a post-processing technical solution of alkaline passivation combined with constant temperature drying and curing treatment, and achieves the technical effect of enhancing the corrosion resistance and stability of the coating by generating a dense protective film on the surface of the coating and further curing its structure. Compared with the technical solution in the prior art that does not fully optimize the post-processing process, it solves the problem that the coating is easily corroded in a high humidity and high salt environment and has poor stability in long-term operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION
[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] Example: Please see attached Figure 1The embodiment of the present invention provides a method for electroplating a plug shielding component, comprising the following steps: step 1, cleaning and activating the surface of the plug shielding component, wherein the cleaning comprises ultrasonic cleaning in an ethanol solution for 8 to 12 minutes at a temperature of 25 to 30°C, and rinsing with deionized water and air-drying after cleaning; the activation treatment comprises treating the surface of the plug shielding component with argon plasma at a pressure range of 0.05 to 0.15 MPa, a power range of 50 to 150 W, and a time of 2 to 5 minutes to remove surface oxides and activate surface chemical activity, and then placing the plug shielding component in a 10% sulfuric acid solution for acidic activation treatment for 1 to 3 minutes at a temperature of 25 to 35°C to further enhance the surface affinity.
[0021] Ultrasonic waves generate microbubbles through cavitation effect, forming a strong local impact force on the surface of the plug shield, effectively removing oil and particles attached to the surface. The cleaning process is controlled by reasonable time and temperature to prevent excessive cleaning from damaging the substrate surface.
[0022] Step 2: The high-energy particles in the plasma impact the surface of the plug shield, which can peel off the oxide layer and impurities on the surface, and at the same time enhance the micro-roughness of the surface through physical etching, providing an excellent bonding interface for subsequent electroplating.
[0023] The acidic environment provided by the sulfuric acid solution can effectively remove the trace impurities remaining on the surface, and at the same time generate a metal surface with high activity and micro-rough structure, laying the foundation for the uniform growth of the subsequent plating layer. The plug shielding part that has undergone surface pretreatment is placed in the electrolyte for electroplating. During the electroplating process, the electric field distribution is regulated by the main electrode and the auxiliary electrode. The main electrode is used to provide a stable current density, and the current density range is 2.0 to 2.5A / dm 2 , the auxiliary electrode is arranged at the edge and groove area of the plug shielding part, which is used to dynamically control the local electric field, and the potential range of the auxiliary electrode is 0-0.5V; during the electroplating process, a magnetic field is used to enhance the migration of metal ions, and the magnetic field is generated by an electromagnetic coil, and the magnetic field strength ranges from 0.2 to 0.4T, and the direction of the magnetic field is orthogonal to the direction of the electric field; in addition, a turbulent flow is generated in the deep hole and groove area of the plug shielding part by a microfluidic nozzle, and the flow rate of the microfluidic nozzle ranges from 0.2 to 0.5m / s, and the nozzle spray angle ranges from 30° to 60°. The electroplating is carried out using a pulse current, the pulse frequency ranges from 300 to 500Hz, and the peak current density is 2.5 to 3.5A / dm 2 The ratio of on-time to off-time is 1:1 to 1:2. The electroplating time is 8 to 12 minutes, and the thickness of the final coating is controlled at 6±0.5μm.
[0024] The distribution regulation of the main electrode and the auxiliary electrode can effectively optimize the current distribution on complex geometric surfaces. The main electrode provides a uniform basic current, while the auxiliary electrode enhances or weakens the electric field in the edge and groove areas, and dynamically regulates the deposition rate of potential balance ions in these areas, thereby solving the problem of uneven thickness of the coating on complex surfaces.
[0025] The magnetic field enhances the lateral migration ability of metal ions through the Lorentz force. Since the direction of the magnetic field is orthogonal to the direction of the electric field, the movement of metal ions perpendicular to the electric field is enhanced, allowing the ions to reach deep holes and grooves more evenly, improving the uniformity of coating coverage on complex geometric surfaces.
[0026] The microfluidic nozzle produces controllable fluid disturbances in key areas, which helps to break the static boundary layer of the plating solution and improve the distribution of metal ions in the electrolyte, especially in recessed and deep hole areas, and effectively improves the ion mass transfer efficiency in these areas by changing the flow rate and injection angle.
[0027] Through pulse current regulation, the current peak in the deposition phase promotes the rapid deposition of metal ions, while the shutdown phase rebalances the distribution of plating solution ions, inhibits dendrite growth and bubble formation, and finally obtains a denser and more uniform coating. Step 3: Passivate, clean, dry and cure the electroplated plug shield, wherein the passivation treatment is carried out in an alkaline passivation solution with a pH value of 9 to 10, and the passivation time is 2 to 4 minutes to form a dense protective film on the surface of the plug shield; after cleaning, place the plug shield in a constant temperature environment of 70 to 90°C and dry for 0.5 to 1 hour to ensure the removal of residual liquid on the surface; finally, perform curing treatment to further improve the stability of the coating.
[0028] The alkaline passivation solution forms a stable oxide film on the surface of the coating through chemical reaction. This film has excellent corrosion resistance and can effectively protect the long-term stability of the coating in complex environments.
[0029] The cleaning process removes chemical residues after electroplating to prevent them from having adverse effects on the performance of the coating; the drying process removes moisture from the surface of the coating at a constant temperature to prevent oxidation or stains on the surface of the coating due to residual liquid.
[0030] The curing process further improves the mechanical strength and corrosion resistance of the coating, while also enhancing the adhesion and crack resistance of the coating.
[0031] Embodiment 1: Standard electroplating process for conventional plug shielding Purpose: To verify the ability of the present invention to achieve a uniform electroplating layer on a conventional plug shielding part, and solve the problem of uneven plating thickness in the background technology.
[0032] Surface pretreatment cleaning: immerse the plug shield in an ethanol solution (concentration ≥ 99.5%) and perform ultrasonic cleaning for 10 minutes at a cleaning temperature of 30° C. Rinse with deionized water and air dry.
[0033] Plasma treatment: introduce argon gas with a gas pressure of 0.1 MPa, a processing power of 100 W, and a time of 3 minutes to remove the surface oxide layer and impurities.
[0034] Acid activation: Place the plug shield in a 10% sulfuric acid solution and soak for 2 minutes at a solution temperature of 30°C. After taking it out, rinse it with deionized water and keep it moist.
[0035] Electroplating process Electrolyte formula: Nickel sulfate: 300g / L; Nickel chloride: 45g / L; Boric acid: 30g / L; Polyethylene glycol (PEG): 50 ppm.
[0036] Electric field control: Main electrode current density: 2.2A / dm 2 ; Auxiliary electrode potential range: 0.3V.
[0037] Magnetic field settings: Magnetic field strength: 0.3T; The direction of the magnetic field is perpendicular to the electric field.
[0038] Flow field optimization: Microfluidic nozzle flow rate: 0.3m / s; Spray Angle: 45°.
[0039] Pulse current setting: Pulse frequency: 400Hz; Peak current density: 3.0A / dm 2 ; Ratio of on time to off time: 1:1.
[0040] Plating time: 10 minutes.
[0041] Post-processing Passivation treatment: The plug shield is placed in an alkaline passivation solution with a pH of 9 for 3 minutes.
[0042] Drying treatment: drying temperature is 80℃ and time is 1 hour.
[0043] Experimental results: The coating thickness uniformity error is ±0.3μm; No corrosion spots after 500 hours of salt spray test; The coating surface is smooth and dense, suitable for general applications.
[0044] Summary of the embodiment: This embodiment achieves uniform thickness of the coating on a conventional plug shield by optimizing the electric field, magnetic field and flow field. Through standardized process conditions, it is verified that the invention is suitable for electroplating requirements in conventional scenarios, and at the same time, it reflects the significant advantages of the invention in improving thickness control accuracy and anti-corrosion performance.
[0045] Embodiment 2: Electroplating process for complex geometric plug shielding Purpose: To verify the electroplating capability of the present invention in complex geometric surfaces (deep holes, grooves, etc.) and solve the problem of insufficient coverage of deep hole areas in the background technology.
[0046] Surface preparation The specific parameters are the same as those in the first embodiment.
[0047] Electroplating process Electrolyte formula: Nickel sulfate: 310g / L; Nickel chloride: 50g / L; Boric acid: 35g / L; Polyethylene glycol (PEG): 60 ppm.
[0048] Electric field control: Main electrode current density: 2.0A / dm 2 ; Auxiliary electrode potential range: 0.4V.
[0049] Magnetic field settings: Magnetic field strength: 0.4T; The direction of the magnetic field is perpendicular to the electric field.
[0050] Flow field optimization: Microfluidic nozzle flow rate: 0.5m / s; Spray Angle: 30°.
[0051] Pulse current setting: Pulse frequency: 300Hz; Peak current density: 3.5A / dm 2 ; Ratio of on time to off time: 1:2.
[0052] Plating time: 12 minutes.
[0053] The post-processing is the same as that in Example 1, and the specific parameters are the same.
[0054] Experimental results: The coating coverage in grooves and deep hole areas is increased by 30%; The coating thickness error is controlled within ±0.4μm; The surface is even with no bare areas.
[0055] Summary of the embodiment: This embodiment significantly improves the coverage of complex geometric surfaces by strengthening the synergistic effect of the magnetic field and the flow field. Compared with the first embodiment, the ion migration ability of the deep hole area is significantly improved, and the coating thickness is slightly increased, which verifies that the present invention is suitable for the application scenario of complex-shaped plug shielding parts.
[0056] Compared with the standard application scenario of the first embodiment, this embodiment optimizes the auxiliary electrode, flow field disturbance and magnetic field strength for complex geometric structures to increase the coverage of ions in deep holes and groove areas, thereby making up for the shortcomings of traditional technology in complex surface treatment.
[0057] Example 3: Optimized high-performance electroplating process Purpose: To verify the ability to improve the corrosion resistance of the coating under more severe working conditions and to solve the problem of insufficient corrosion resistance in the prior art.
[0058] Surface preparation The specific parameters are the same as those in the first embodiment.
[0059] Electroplating process Electrolyte formula: Nickel sulfate: 290g / L; Nickel chloride: 50g / L; Boric acid: 30g / L; Add sodium chloride: 0.02M (to increase the conductivity of the solution).
[0060] Electric field control: Main electrode current density: 2.5A / dm 2 ; Auxiliary electrode potential range: 0.3V.
[0061] Magnetic field settings: Magnetic field strength: 0.2T; The direction of the magnetic field is perpendicular to the electric field.
[0062] Flow field optimization: Microfluidic nozzle flow rate: 0.4m / s; Spray Angle: 60°.
[0063] Pulse current setting: Pulse frequency: 500Hz; Peak current density: 3.0A / dm 2 ; Ratio of on time to off time: 1:1.
[0064] Plating time: 10 minutes.
[0065] Post-processing Passivation treatment: The plug shield is placed in a passivation solution with a pH of 10 for 4 minutes.
[0066] Drying and curing treatment: drying temperature is 90°C for 1 hour; followed by curing treatment at 200°C for 20 minutes.
[0067] Experimental results: No corrosion after 1000 hours of salt spray test; The bonding strength of the coating is increased by 25%; The micro porosity is reduced by 50% and the wear resistance of the coating surface is enhanced.
[0068] Summary of the embodiment: This embodiment significantly improves the anti-corrosion performance and mechanical strength of the coating by optimizing the electrolyte and post-treatment process. Compared with the first and second embodiments, it is suitable for the application of plug shielding components under harsh working conditions such as high humidity and high salt.
[0069] Compared with Examples 1 and 2, this embodiment adds sodium chloride to the electrolyte to enhance conductivity, and adopts a higher post-processing temperature and curing step, thereby further improving the density and corrosion resistance of the coating.
[0070] Comparative Example 1: Surface preparation Cleaning is done by simple distilled water rinsing, without ultrasonic cleaning or plasma treatment, and only by solvent wiping to remove surface impurities.
[0071] The acid activation treatment used a 5% sulfuric acid solution with an activation time of 1 minute and no temperature control.
[0072] Electroplating process Electrolyte formula: the same as in Example 1.
[0073] Electric field control: only single main electrode is used, current density is 2.2A / dm 2 , without auxiliary electrode regulation.
[0074] Magnetic field setting: No magnetic field applied.
[0075] Flow field optimization: the electrolyte is still and there is no fluid disturbance.
[0076] Pulse current setting: constant DC current is used, without pulse current regulation.
[0077] Plating time: 10 minutes.
[0078] Post-processing The pH of the passivation solution was 8, and the treatment time was 2 minutes; The drying conditions are drying at room temperature, without constant temperature drying.
[0079] Surface preparation Rinse the surface with distilled water, without ultrasonic cleaning and plasma treatment.
[0080] The acid activation is consistent with that in Example 2.
[0081] Electroplating process Electrolyte formula: the same as in Example 2.
[0082] Electric field control: The main electrode and auxiliary electrode were used, but the auxiliary potential was not optimized for the groove and deep hole areas, and the auxiliary electrode potential was fixed at 0.2V.
[0083] Magnetic field setting: A magnetic field is used, but the intensity is fixed at 0.1T without dynamic adjustment.
[0084] Flow field optimization: The microfluidic nozzle is removed, the electrolyte has no turbulence, and ion transport is performed only by natural convection.
[0085] Pulse current setting: the same as that of the second embodiment.
[0086] Plating time: 12 minutes.
[0087] The post-processing passivation and drying treatment are consistent with that in Example 2.
[0088] Comparative Example 3: The surface pretreatment is consistent with that in Example 3.
[0089] Electroplating process Electrolyte formula: No sodium chloride is added, only nickel sulfate, nickel chloride and boric acid are used.
[0090] Electric field control: The main electrode current density is fixed at 2.2A / dm 2 , without auxiliary electrode.
[0091] Magnetic field setting: No magnetic field applied.
[0092] Flow field optimization: microfluidic nozzle removed, electrolyte natural convection.
[0093] Pulse current setting: the same as that of embodiment 3.
[0094] Plating time: 10 minutes.
[0095] Post-processing The pH of the passivation solution was 8.5, and the treatment time was 1 minute; The drying temperature was reduced to 60°C for 30 minutes; No curing step.
[0096] Comparative Example 4: Another comparative experiment based on Example 1 The surface pretreatment is consistent with that in Example 1.
[0097] Electroplating process Electrolyte formula: the same as in Example 1.
[0098] Electric field control: same as in the first embodiment.
[0099] Magnetic field setting: same as in Example 1.
[0100] Flow field optimization: same as in Example 1.
[0101] Current setting: constant DC current, current density is 2.5A / dm 2 .
[0102] Plating time: 10 minutes.
[0103] The post-processing is consistent with that in Example 1.
[0104] Comparative Example 5: The surface pretreatment is consistent with that of Example 2.
[0105] Electroplating process Electrolyte formula: the same as in Example 2.
[0106] Electric field control: same as in the second embodiment.
[0107] Magnetic field settings: The magnetic field was fixed at 0.2 T, and the magnetic field strength was not optimized for complex surface areas.
[0108] Flow field optimization: microfluidic nozzle removed, electrolyte natural convection.
[0109] Pulse current setting: the same as that of the second embodiment.
[0110] Plating time: 12 minutes.
[0111] The post-processing is consistent with that in Example 2.
[0112] Experimental Example 1: The purpose of the experiment is to verify the ability of the present invention to achieve uniform coating on the surface of the plug shield, and to highlight the effect of multi-physical field collaborative optimization and flow field disturbance technology in improving coating uniformity by comparing the coating thickness errors of the embodiment and the comparative example.
[0113] Experimental materials and equipment Plug shield samples: conventional plug shields and complex geometry plug shields; Laser thickness gauge (resolution: 0.1 μm); Samples prepared in Example 1 and Example 2; Samples prepared in Comparative Examples 1 and 2.
[0114] Experimental procedures Sample preparation Take the plug shielding samples prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 respectively.
[0115] Each group of samples includes five representative plug shields at different locations (flat surface, edge, groove).
[0116] Measurement location selection Ten test points were selected on the plane, edge and groove of each sample, and a total of 30 test points were measured.
[0117] Mark each test point location to ensure measurement repeatability.
[0118] Thickness measurement: Use a laser thickness gauge to measure the coating thickness at each test point and record the average value of 3 repeated measurements.
[0119] Data analysis: Calculate the thickness uniformity error (the difference between the maximum thickness and the minimum thickness) of each group of samples.
[0120] The thickness errors of the embodiment and the comparative example were compared, and the effects of multi-physics field optimization and flow field disturbance on uniformity were analyzed.
[0121] Experimental data Experimental Summary This experiment verifies the technical advantage of the present invention in improving the uniformity of the thickness of the plug shielding component by comparing the thickness uniformity of the embodiment and the comparative example samples. The experimental results show that the thickness errors of embodiment 1 and embodiment 2 are 0.6μm and 0.5μm, respectively, which are significantly lower than 1.7μm and 1.5μm of comparative example 1 and comparative example 2. The results show that multi-physics field collaborative optimization and flow field disturbance technology have obvious advantages in reducing the error of the coating thickness and improving uniformity.
[0122] The multi-physics field optimization technology of the present invention forms a dynamic electric field distribution between the main electrode and the auxiliary electrode, effectively reducing excessive deposition in the edge area and insufficient deposition in the groove area. At the same time, the magnetic field and the electric field act orthogonally, promoting ion migration through the Lorentz force, and further improving the uniformity of metal ion distribution on complex surfaces. The introduction of flow field disturbances, through the local disturbances generated by the microfluidic nozzle, breaks the boundary layer effect of the plating solution and increases the ion transmission efficiency in the deep hole and groove area.
[0123] The test results of Comparative Examples 1 and 2 show that in the absence of multi-physics field collaborative optimization and flow field disturbance, the edge area is deposited too thickly, while the groove area is insufficiently deposited. The unevenness of the coating thickness mainly stems from the limitations of traditional static electric field distribution and natural convection, which cannot solve the problem of uneven ion distribution under complex surface geometric structures. In contrast, the present invention significantly improves the uniformity of the coating through dynamic regulation in the embodiments, solving the key pain points in the traditional electroplating process.
[0124] Experimental Example 2: Deep hole area coating coverage test Experimental Description Purpose The technical advantages of the present invention in coating coverage ability on complex geometric surfaces (especially deep holes and groove areas) are verified, and the influence of multi-physical field optimization (magnetic field and flow field) on coating coverage performance is analyzed by comparing the samples of the embodiment and the comparative example.
[0125] Experimental materials and equipment Plug shield samples: Plug shields with complex geometry; Scanning electron microscope (SEM): resolution 0.01 μm; Samples prepared in Example 2; Samples prepared in Comparative Examples 2 and 5.
[0126] Experimental procedures Sample preparation The complex geometric structure plug shielding components prepared in Example 2, Comparative Example 2 and Comparative Example 5 were respectively taken.
[0127] Each set of samples includes plug shields with deep hole areas ranging from 1mm to 2mm in diameter, ensuring consistency of the complex surfaces tested.
[0128] Coating morphology observation A scanning electron microscope (SEM) was used to photograph the coating morphology in the deep hole area to observe the continuity and thickness of the coating on the deep hole surface and whether there was an uncovered area.
[0129] Five observation points were randomly selected inside each deep hole, and the coating thickness at each point was measured and recorded.
[0130] Coverage calculation Based on the SEM images, the coverage of the deep hole surface coating (the ratio of the coating area to the total surface area of the deep hole) was calculated using image analysis software.
[0131] Calculate the average coverage for each group of samples.
[0132] Experimental data.
[0133] This experiment verifies the technical advantages of the present invention in deep hole and complex geometric surface electroplating by comparing the coating coverage of Example 2 with Comparative Example 2 and Comparative Example 5. The coating coverage of the sample of Example 2 reaches more than 98%, while the coverage of Comparative Example 2 and Comparative Example 5 is 72% and 84% respectively, which is significantly lower than that of Example 2. This result shows that multi-physics field optimization technology (magnetic field and flow field) plays a key role in improving the coating coverage ability of deep hole areas.
[0134] The magnetic field optimization of the present invention enhances the lateral migration ability of metal ions through the Lorentz force, so that they can be more evenly distributed inside the deep hole, while the flow field disturbance breaks the static boundary layer of the plating solution through the microfluidic nozzle, further improving the ion transmission efficiency in the deep hole area. The synergistic effect of the two forms a uniform deposition environment in a complex geometric structure, effectively solving the problem of insufficient deposition in the deep hole area in traditional electroplating.
[0135] The experimental results of comparative example 2 show that due to the lack of flow field perturbation technology, the metal ion concentration inside the deep hole cannot be kept uniform, resulting in a significant decrease in the coating coverage. Although comparative example 5 uses flow field perturbation technology, no magnetic field is applied, the ion migration ability in the deep hole is still limited, the coating thickness is uneven, and there are some uncovered areas. In contrast, the present invention in Example 2 fundamentally improves the coverage performance of complex geometric surfaces and deep hole areas through the coordinated optimization of magnetic field and flow field.
[0136] In addition, the thickness measurement in the experimental data further supports this conclusion: the uniformity of the coating thickness of Example 2 is significantly higher than that of Comparative Examples 2 and 5, indicating that multi-physics field optimization can effectively improve the quality and continuity of the coating in the deep hole area. Through the comparison of this experiment, the technical advantages and practical application value of the present invention in complex surface applications are fully verified.
[0137] Experimental Example 3: Plating Density Test Experimental Description Purpose The optimization effect of the pulse current process on the density and grain uniformity of the coating is verified, and the role of the pulse current in improving the quality of the coating is analyzed by comparing Example 1 with Comparative Example 4.
[0138] Experimental materials and equipment Plug shield samples: conventional geometry plug shield; X-ray diffractometer (XRD): used to test the grain size and crystal orientation of the coating; Micro porosity analysis equipment: used to calculate the porosity of the coating; Sample prepared in Example 1; Sample prepared in Comparative Example 4.
[0139] Experimental procedures Sample preparation The conventional geometry plug shielding samples prepared in Example 1 and Comparative Example 4 were respectively taken, with 5 samples in each group, ensuring the same process conditions and materials.
[0140] Grain size test X-ray diffractometer (XRD) was used to measure the grain size of the sample coating.
[0141] The scanning range was set to 2θ = 20°-90°, the peak position and full width at half maximum (FWHM) were recorded, and the grain size was calculated (using the Scherrer formula).
[0142] Select 3 points in the plane area of each sample and take the average value.
[0143] Porosity test The porosity of the sample coating was measured using a micro-porosity analysis device.
[0144] Five areas were selected on the sample surface, and the ratio of pore area to total surface area was calculated using image processing software.
[0145] Data analysis The grain size uniformity and porosity of the embodiment and the comparative example were compared to analyze the effect of the pulse current on optimizing the density of the coating.
[0146] Experimental data.
[0147] This experiment verifies the effect of pulse current on improving the density and grain uniformity of the coating by comparing the grain size and porosity of the coating of Example 1 and Comparative Example 4. The experimental results show that the average grain size of the sample of Example 1 is 46.2nm, which is significantly smaller than 70.3nm of Comparative Example 4, and the porosity is also significantly reduced to 0.93%, which is much lower than 3.17% of Comparative Example 4. The results show that pulse current has a significant optimization effect on the coating structure.
[0148] The present invention adopts pulse current technology to control the deposition rate of metal ions by adjusting the peak current density and pulse switching time. In the power-on stage, metal ions are deposited at a high kinetic rate to form dense crystals, while in the off stage, the metal ions in the electrolyte are redistributed evenly, avoiding coarse grains and structural defects caused by too fast deposition. At the same time, the transient electric field fluctuation of the pulse current effectively inhibits the growth of dendrites and the formation of pores, making the coating more dense and uniform.
[0149] The experimental results of comparative example 4 show that under the condition of constant DC current, metal ions continue to deposit, and the deposition rate is too fast, resulting in the inability to completely rearrange the grains during the growth process, forming coarse crystal particles. At the same time, due to the lack of a shutdown phase of the DC current, the transmission of metal ions in the plating solution is limited, and micropores are easily formed in the coating, reducing the overall density. These results clearly show that constant current cannot effectively optimize the internal structure of the coating.
[0150] The comparative analysis of this experiment fully demonstrates the core role of pulse current technology in the present invention. Compared with traditional DC electroplating, pulse current achieves finer grain control and lower porosity by dynamically regulating the deposition process of ions, significantly improving the density and mechanical strength of the coating, thereby better meeting the actual application requirements of high-performance plug shielding parts.
[0151] Experimental Example 4: Corrosion Resistance Test The purpose of the experiment is to verify the technical advantages of the present invention in improving the corrosion resistance of the coating, and to analyze the contribution of post-treatment optimization (passivation, drying and curing) to the corrosion resistance of the coating by comparing Example 3 with Comparative Example 3.
[0152] Experimental materials and equipment Plug shield samples: conventional geometry plug shield; Salt spray test chamber: in accordance with ASTMB117 standard; Samples prepared in Example 3; Samples prepared in Comparative Example 3.
[0153] Experimental procedures Sample preparation The plug shielding samples prepared in Example 3 and Comparative Example 3 were respectively taken, with 5 samples in each group, to ensure the same coating thickness and pre-process conditions.
[0154] Salt spray test The corrosive environment was simulated in a salt spray test chamber. The test solution was 5% sodium chloride solution and the temperature was set at 35°C.
[0155] According to ASTM B117 standard, the samples were placed in a salt spray environment for 500 hours.
[0156] Corrosion area calculation The samples were taken out every 100 hours, cleaned and dried, and the sample surface images were taken using a high-resolution digital camera.
[0157] The corrosion area ratio (the ratio of the corrosion area to the total surface area) was calculated using image processing software.
[0158] Data analysis The corrosion area ratios of the examples and comparative samples after 500 hours of salt spray test were compared to analyze the effect of post-treatment on the anti-corrosion performance of the coating.
[0159] Experimental data This experiment verified the significant effect of optimizing post-processing technology (passivation, drying and curing) on improving the corrosion resistance of the coating by comparing the salt spray test results of Example 3 with those of Comparative Example 3. The experimental results show that the corrosion area of Example 3 is only 1.0% after 500 hours of salt spray test, while the corrosion area of Comparative Example 3 is as high as 8.5%. The results show that post-processing optimization technology plays an important role in improving the corrosion resistance of the coating.
[0160] The present invention adopts alkaline passivation treatment in post-treatment to generate a dense oxide film through chemical reaction, which not only improves the corrosion resistance of the coating, but also provides additional barrier protection for the coating. In addition, the constant temperature drying step further removes the residual liquid and gas on the surface of the coating, reduces the formation of micropores, and avoids the penetration of corrosive media. The curing treatment promotes the structural stability and chemical bond strengthening inside the coating by heating, which significantly improves the durability of the coating in a high-salt and high-humidity environment.
[0161] The results of comparative example 1 show that in the absence of optimized post-treatment, tiny pores and defects are easily formed on the surface of the coating, which become channels for the penetration of corrosive media and accelerate the corrosion of the coating. At the same time, due to the lack of effective curing treatment, the internal structure of the coating is relatively loose and it is difficult to resist corrosion in a long-term salt spray environment. This result is in sharp contrast to Example 3, further proving the key role of post-treatment optimization in corrosion resistance.
[0162] Through the comparative analysis of this experiment, it is clear that the present invention optimizes the anti-corrosion performance of the coating from both physical and chemical levels through scientifically designed passivation, drying and curing steps, solves the problem of easy corrosion and performance degradation of the coating in a high-salt and high-humidity environment in the traditional process, and provides technical guarantee for high-durability plug shielding parts. The significant difference in experimental data fully demonstrates the superiority of the present invention in practical application scenarios.
[0163] Experimental Example 5: Actual application performance testing Purpose The comprehensive performance of the present invention in practical applications, including the bonding strength, wear resistance and stability of the coating in high temperature and high humidity environments, is verified. By comparing Example 1 and Example 3 with Comparative Example 1 and Comparative Example 3, the improvement of practical application performance by multi-physical field optimization technology and post-processing technology is analyzed.
[0164] Experimental materials and equipment Plug shielding parts samples: conventional structure plug shielding parts; Tensile testing machine: test the bonding strength; Wear-resistant testing machine: test the wear-resistant performance of the coating; High temperature and high humidity cycle test equipment: test the thermal cycle stability of the coating; Samples prepared in Example 1 and Example 3; Samples prepared in Comparative Examples 1 and 3.
[0165] Experimental procedures Sample preparation The plug shielding components prepared in Example 1, Example 3, Comparative Example 1 and Comparative Example 3 were respectively selected, with 5 samples in each group, to ensure the same base material and coating thickness.
[0166] Bonding strength test A tensile testing machine was used to test the bonding strength between the coating and the substrate.
[0167] Perform a tensile test on each sample and record the critical tensile force (N / cm 2 ).
[0168] Each sample was tested 3 times and the average value was taken.
[0169] Wear resistance test The friction test of the coating surface was carried out using a wear tester.
[0170] Each sample was subjected to 2000 reciprocating frictions, with the friction head applying a load of 2N and a friction speed of 60 times / min.
[0171] After the test, observe the wear condition of the coating surface and calculate the wear area.
[0172] Thermal Cycle Test The samples were subjected to 10 thermal cycle tests using a high temperature and high humidity cycle test equipment.
[0173] Each cycle includes a 100°C high temperature environment and a 40°C high humidity environment, each lasting 30 minutes.
[0174] After the test, record whether there are cracks, peeling and other defects on the coating surface.
[0175] This experiment compares the bonding strength, wear resistance and thermal cycle stability of the examples and the comparative examples to verify the improvement of the practical application performance by multi-physics field optimization technology and post-processing process. The experimental results show that the comprehensive performance of the examples 1 and 3 is significantly better than that of the comparative examples 1 and 3, especially in terms of bonding strength and wear resistance. The bonding strength of the example 3 reaches 135N / cm 2 , the wear area is only 0.6mm 2 , showing extremely high stability, while the bonding strength and wear resistance of comparative example 3 are poor, and cracks and peeling are obvious.
[0176] The present invention realizes uniform electric field and stable flow field through multi-physical field optimization, so that the deposition of the coating on the surface of the substrate is more uniform and compact. The pulse current technology further improves the deposition control ability of metal ions, refines the grain size, and enhances the mechanical bonding force of the coating. In the post-processing process, the passivation reaction generates a dense protective film on the surface of the coating, and drying and curing further improve the wear resistance and crack resistance of the coating. This multi-level optimization process ensures the reliability of the coating in practical applications.
[0177] The experimental results of comparative examples 1 and 3 show that in the absence of multi-physics field optimization technology, the uneven distribution of the electric field leads to a decrease in the bonding strength of the coating, an increase in surface defects, and a weakening of the wear resistance. In addition, the unoptimized post-treatment process causes more micropores and cracks on the surface of the coating, which easily causes peeling and cracking in the thermal cycle test, making it difficult to adapt to the challenges of high temperature and high humidity environments.
[0178] The comparative results of this experiment fully demonstrate the remarkable effect of the present invention in improving the comprehensive performance of the coating. The improvement of bonding strength and wear resistance makes the plug shield more adaptable to high-load and long-life application requirements, while the thermal cycle stability verifies the reliability of the coating of the present invention in extreme environments, providing strong support for practical industrial applications. The significant difference in experimental data shows that the present invention has strong practical application value and solves the technical bottleneck of insufficient durability in traditional processes.
[0179] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for electroplating a plug shield, characterized in that: The following steps are involved: Performing surface pretreatment on the plug shield; Placing the plug shield in an electrolyte for electroplating, wherein the electric field distribution is regulated by a main electrode and an auxiliary electrode during the electroplating process, and the magnetic field and the flow field are combined for optimization; The electroplated plug shield is passivated, cleaned, dried and cured.
2. The electroplating method of a plug shield according to claim 1, characterized in that: The surface pretreatment comprises the following steps: Ultrasonic cleaning is performed in an ethanol solution for 8 to 12 minutes at a temperature of 25 to 30°C; The surface of the plug shield is treated using argon plasma, with a pressure range of 0.05 to 0.15 MPa, a power range of 50 to 150 W, and a time of 2 to 5 minutes; Carry out acid activation treatment in 10% sulfuric acid solution for 1 to 3 minutes at a temperature of 25 to 35°C.
3. The electroplating method of a plug shield according to claim 1, characterized in that: In the electroplating step, the main electrode is used to provide a stable current density in the range of 2.0 to 2.5 A / dm²; the auxiliary electrode is arranged at the edge and groove area of the plug shielding part to dynamically control the local electric field, and the auxiliary electrode potential range is 0 to 0.5 V.
4. The electroplating method of a plug shield according to claim 1, characterized in that: In the electroplating step, the components of the electrolyte include: Nickel sulfate, concentration is 280-320 g / L; Nickel chloride, concentration is 40-50 g / L; Boric acid, concentration is 25-35 g / L; Polyethylene glycol, concentration is 40-60ppm.
5. The electroplating method of a plug shield according to claim 1, characterized in that: In the electroplating step, a magnetic field is used to enhance ion migration. The magnetic field is generated by an electromagnetic coil, the magnetic field strength ranges from 0.2 to 0.4 T, and the direction of the magnetic field is orthogonal to the direction of the electric field.
6. The electroplating method of a plug shield according to claim 1, characterized in that: In the electroplating step, a turbulent flow is generated in the deep hole and groove area of the plug shielding part by a microfluidic nozzle, the flow rate of the microfluidic nozzle ranges from 0.2 to 0.5 m / s, and the nozzle spray angle ranges from 30° to 60°.
7. The electroplating method of a plug shield according to claim 1, characterized in that: The electroplating step adopts pulse current for electroplating, the pulse frequency range is 300-500Hz, the peak current density is 2.5-3.5A / dm², and the ratio of on time to off time is 1:1-1:
2.
8. The electroplating method of a plug shield according to claim 1, characterized in that: The electroplating time is 8 to 12 minutes, and the thickness of the final coating is controlled at 6±0.5 μm.
9. The electroplating method of a plug shield according to claim 1, characterized in that: The passivation treatment in the post-treatment is carried out in an alkaline solution with a pH value of 9 to 10, and the passivation time is 2 to 4 minutes.
10. The electroplating method of a plug shield according to claim 1, characterized in that: The drying treatment in the post-treatment is carried out at a constant temperature of 70 to 90° C. for 0.5 to 1 hour.
Citation Information
Patent Citations
Electromachining device and electromachining method for picking spindle of cotton picker
CN115821347A
Local gold plating process for laser pumping source chip base not prone to peeling
CN118957692A